Brain state transitions network: Topology and economy of the brain dynamics in schizophrenia - Ramírez - Mahaluf; Juan (2023)
3 To analyze the relation between global efficiency, cost and cost-efficiency of the meta-states transitions network in patients with anti-NMDAR encephalitis with clinical features, specifically cognitive dysfunction and compare them to patients with schizophrenia, in order to understand common mechanisms associated to glutamate dysfunction. TOTAL Resting-state functional MRI data were acquired in 73 patients with NMDAR encephalitis and 73 age- and sex-matched healthy controls. Time-resolved functional connectivity was clustered into brain meta-states, giving rise to a time-resolved transition network graph with states as nodes and transitions between brain meta-states as weighted, directed edges. Network topology, robustness, and transition cost of these transition networks were compared between groups. Transition networks of patients showed significantly lower local efficiency, lower robustness and higher leap size compared to controls. These metrics were correlated with disease severity and disease duration. Otro(s) aspecto(s) que Ud. considere importante(s) en la evaluación del cumplimiento de objetivos planteados en la propuesta original o en las modificaciones autorizadas por los Consejos. En adición a los objetivos del proyecto, inicialmente se trabajo en completar el análisis y publicar la metodología propuesta en el presente proyecto. En el proyecto postulado se presentaron resultados preliminares en participantes sanos. Sin embargo para la publicación final se aumento el tamaño de la muestra y se replicaron los resultados en una segunda cohorte de participantes sanos reclutados por nuestro grupo de investigación. En adición se realizaron análisis adicionales como la incorporación de otros modelos nulos para darle robustez a la metodología, la caracterización de meta-estados mas visitados (hubs) y análisis de costo estático. Como producto, este trabajo fue publicado en la revista Neuroimage con el titulo "Transitions between human functional brain networks reveal complex, cost-efficient and ...